Effects of different training intensity distributions on endurance capacity in breast and prostate cancer survivors: a randomized controlled trial - Bauer, Nikolai; Schneider, Justine; Schlüter, Kathrin; Wiskemann, Joachim; Rosenberger, Friederike (European journal of sport science, 2025)
This study aimed to compare the effects of isocaloric polarized and threshold training intensity distribution on endurance capacity in breast and prostate cancer survivors. A total of 28 breast and 27 prostate cancer survivors were randomly assigned to a polarized (POL, n = 27 (13 women), age 60 ± 8 years, peak oxygen uptake (VO2peak) 23 mL·min−1 kg−1), or threshold training group (ThT, n = 28 (15 women), age 59 ± 10 years, VO2peak 23 mL·min−1 kg−1) who completed two sessions per week on a cycle ergometer over 12 weeks. Exercise duration was adapted to obtain equivalent energy expenditure in both groups. Cardiopulmonary exercise and verification tests were performed to determine endurance capacity (VO2peak, peak power output (PPO), ventilatory threshold (VT1), blood lactate thresholds (LT1 and IAT)), and maximal exhaustion. POL did not achieve the planned polarized intensity distribution and rather performed a pyramidal training. Pyramidal and threshold training significantly (p < 0.001) improved endurance capacity regarding VO2peak (0.09 and 0.12 L·min−1), PPO (27 and 17W), power output at VT1 (11 and 13W), oxygen uptake at VT1 (0.09 and 0.11 L·min−1), power output at LT1 (7 and 12W), and power output at IAT (12 and 14W). No difference was found between groups, but ThT required significantly (p < 0.001) less time than pyramidal training to achieve the described improvements (59 ± 1 min/week vs. 76 ± 11 min/week). Comparison of isocaloric training intensity distributions revealed no significant differences between groups (Pyramidal: 170 ± 43 kJ/session, ThT: 175 ± 35 kJ/session, p = 0.10). Pyramidal and isocaloric threshold training resulted in comparable effects on endurance capacity in cancer survivors, with ThT requiring significantly less time for these effects.
Gesehen am 13.11.2025